Thorac Res Pract 2023
DOI: 10.5152/thoracrespract.2023.22058
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Assessment of the Continuous Health Care Provided to COVID-19 Patients Consulted Via Videoconference

Abstract: Objective: Telemedicine has been defined as a valuable tool in delivering care for COVID-19 patients. However, clinicians and policymakers should be convinced that traditional and new technological methods of clinical management may be equally effective. The purpose of this study was to generate some initial recommendations based on the clinical utility of videoconference consultation in forward triage and follow-up for COVID-19 patients. Material and Methods: This retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The proposed scenario can be applied to different telematic platforms that are commonly used and easily available. Specifically, the software recommended in the implementation phase within the illustrated document is Skype™ [ 13 ], as it is free and widely accessible throughout the country. Numerous studies and international scientific experiences have demonstrated the validity of this platform in healthcare settings, having been applied for various purposes with encouraging results: virtual rehabilitation interventions for language disorders, remote synchronous consultations in Ophthalmic Telesurgery, health status monitoring following different kinds of interventions, psychotherapy, virtual consultations in Plastic Surgery, as well as in several clinical settings [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The proposed scenario can be applied to different telematic platforms that are commonly used and easily available. Specifically, the software recommended in the implementation phase within the illustrated document is Skype™ [ 13 ], as it is free and widely accessible throughout the country. Numerous studies and international scientific experiences have demonstrated the validity of this platform in healthcare settings, having been applied for various purposes with encouraging results: virtual rehabilitation interventions for language disorders, remote synchronous consultations in Ophthalmic Telesurgery, health status monitoring following different kinds of interventions, psychotherapy, virtual consultations in Plastic Surgery, as well as in several clinical settings [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Synchronized randomization into the control and telemedicine groups was not feasible due to the necessity of implementing telemedicine as video counseling during the pandemic, when the traditional method had to be interrupted, as was the case in similar facilities. If telemedicine had not been voluntarily implemented in the pulmonary outpatient clinic, 4 it would not have been possible to continue smoking cessation support. Under these circumstances, the comparison can be considered acceptable, given that the traditional control group provided data from the smoking cessation support given during the prepandemic period by the same team and structured process.…”
Section: Discussionmentioning
confidence: 99%
“…Only patients who absolutely needed an in-person visit for either physical examination, testing, or prescription were invited to the hospital. 4 After gaining significant experience employing telemedicine for remote management of pulmonary diseases, the pulmonologist noticed the absence of the routine smoking cessation support provided in the prepandemic period. Considering the lower need for urgent physical examinations and laboratory tests, as well as the availability of relevant drugs free of charge from units designated by the Ministry of Health (MoH), the suitability of using telemedicine techniques for smoking cessation support was deemed reasonable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation